Obstetric and Gynecological Outcomes in Patients with STAT3-deficient Hyper IgE Syndrome [13Q]. (May 2018) - Chepa-Lotrea, Xenia; Urban, Amanda; Bergerson, Jenna; Weisman, Hannah; Stratton, Pamela; Freeman, Alexandra
Abstract : INTRODUCTION: Autosomal dominant Hyper IgE syndrome (AD-HIES) is a primary immunodeficiency due to STAT3 mutations, resulting in eczema, recurrent skin and pulmonary infections, and mucocutaneous candidiasis. Little is known of gynecologic-obstetric complications but with improved therapies, women are living longer making reproductive health more pertinent. METHODS: We prospectively interviewed and retrospectively reviewed medical records of adult women with AD-HIES evaluated at NIH between 2000-2017. RESULTS: Of 60 patients aged 19-66 years (mean 35), 45 women were interviewed, and chart reviews were performed on 15, of whom eight were deceased. 21/60 (35%) reported having regular cervical cytology testing with seven (33%) having abnormal squamous cells of unknown significance (ASCUS). Five women reported vulvar cysts/abscesses requiring drainage. Nine women had IUDs placed, in some to suppress menses-associated vulvar eczema/abscess flares; no infectious complications were reported. Over 30% of women chose not to conceive given underlying disease. Of 16 women with pregnancies, 15 women had 26 live births, 6/16 (38%) had miscarriages, and 3/16 (19%) experienced recurrent pregnancy loss. . Three women whose pulmonary symptoms worsened during pregnancy were diagnosed with progression of parenchymal lung disease post-partum. One woman experienced worsening of skin manifestations. Other reported postpartum complications included one incisional infection (after Caesarean) and one hemorrhage leading to hysterectomy. CONCLUSION: As women with AD-HIES are living longer, they elect to have children or prevent pregnancy; knowledge of their reproductive choices and complications can improve their care. While these women may choose to attempt pregnancy, the risk of recurrent pregnancy loss and worsening disease warrants discussion.